Catalyst-and organic solvent-free synthesis, structural, and theoretical studies of 1-arylidenamino-2,4-disubstituted-2-imidazoline-5-ones - Wessam Saaed (Results in Chemistry, 2020)
We have developed a solvent- and catalyst-free cyclization reaction for the synthesis of 1-arylidenamino-2,4-disubstituted-2-imidazoline-5-ones under neat conditions. The new synthetic procedure is efficient and green in nature. All synthesized compounds were obtained in good yields (70–78%) and have been characterized by 1H and 13C NMR spectroscopy. The structure of compound 2d was characterized crystallographically using a single crystal X-Ray diffractometer. Compound 2d was found to crystallize in the triclinic space group P-1 with Z = 2. Moreover, the Frontier Molecular Orbitals (FMOs), the global chemical reactivity descriptors, and the molecular Electrostatic Potential (MEP) of 2d have been calculated at B3LYP/6-31G(d,p) level of theory.